Characterizing indigenous plant growth promoting bacteria and their synergistic effects with organic and chemical fertilizers on wheat (Triticum aestivum) - Asghar, Israr; Ahmed, Maqsood; Farooq, Muhammad Ansar; Ishtiaq, Muhammad; Arshad, Muhammad; Akram, Muhammad; Umair, Adnan; Alrefaei, Abdulwahed Fahad; Jat Baloch, Muhammad Yousuf; Naeem, Aamna (Frontiers in Plant Science, 2023)
The excessive use of chemical fertilizers is deteriorating both environment and soil making it a big challenge faced by sustainable agriculture. To assist the efforts for the solution of this burning issue, nine different potential native strains of Plant Growth Promoting Bacteria (PGPB) were isolated that were characterized morphologically, biochemically and molecularly on the basis of 16S rRNA sequencing namely, SA-1(Bacillus subtilis), SA-5(Stenotrophomonas humi),SA-7(Azospirillum brasilense), BH-1(Azospirillum oryzae), BH-7(Azotobacter armeniacus), BH-8(Rhizobium pusense), BA-3(Azospirillum zeae), BA-6(Rhizobium pusense) and BA-7(Pseudomonas fragi). Furthermore, the capability of indigenous PGPB in wheat (Triticum aestivum, Chakwal-50) under control, DAP+FYM, SA-1,5,7, BH-1,7,8, BA-3,6,7, DAP+ FYM + SA-1,5,7, DAP+FYM+ BH-1,7,8 and DAP+FYM+ BA-3,6,7 was assessed in randomized complete block design (RCBD). The results of the study showed that there was a significant increase in plant growth, nutrients, quality parameters, crop yield and soil nutrients at three depths under SA-1,5,7, BH-1,7,8, BA-3,6,7 in combination with DAP+FYM. Out of all these treatments, DAP+ FYM + BA-3,6,7 was found to be the most efficient for wheat growth having a highest 1000 grain weight of 55.1 g. The highest values of plant height, no. of grains/spike, spike length, shoot length, root length, shoot dry weight, root dry weight, 1000 grain weight, biological yield and economic yield were found to be 90.7 cm, 87.7 cm, 7.20 cm, 53.5 cm, 33.5 cm, 4.87 g, 1.32 g, 55.1 g, 8209 kg/h and 4572 kg/h in treatment DAP+FYM+BA. The treatment DAP+FYM+BA had highest values of TN (1.68 µg/mL), P (0.38%) and K (1.33%). Likewise, the value of mean protein (10.5%), carbohydrate (75%), lipid (2.5%) and available P (4.68 ppm) was also highest in DAP+FYM+BA combination. C:P was found to be significantly highest (20.7) in BA alone but was significantly lowest (11.9) in DAP+FYM+BA. Hence, the integration of strains BA-3, BA-5 and BA-7 in fertilizers can be regarded as the most suitable choice for agricultural growth in the sub-mountainous lower region of AJK. This could serve as the best choice for sustainable wheat growth and improved soil fertility with lesser impacts on the environment.